Factors associated with burnout among dentists in public hospitals, southern Thailand - Seeda Na Nakorn; Wisarut Srisintorn; Nattaporn Youravong (Elsevier, 2022)
Background/purpose: Physician burnout is now a public health crisis and dentist is a stressful professional health occupation. The purpose of this cross-sectional study was to determine the level of burnout and related factors among 423 Thai dentists working in public hospitals, southern Thailand. Materials and methods: A self-administered questionnaire was collected through an online platform and included 5 parts: general information, work information, 22-item Maslach Burnout Inventory-Human Services Survey (MBI-HSS), 23-item Thai Effort-Reward Imbalance Questionnaire (Thai ERIQ), and the Utrecht Work Engagement Scale-9 (UWES-9). The data were analyzed for descriptive statistics - frequency, percentage, mean, standard deviation - and inferential statistics using binary logistic regression. Results: The prevalence of medium to high level of burnout were 45.8%, 44.3%, 4.0% for emotional exhaustion, depersonalization, and low personal accomplishment, respectively. Regarding to the multivariate analysis, the statistically significant factors associated with emotional exhaustion were age, work engagement, workplace relationship, work effort, work reward, grade point average, and workplace consultant. The factors associated with depersonalization were age, work engagement, workplace relationship, work effort, and job reselection. The factors associated with personal accomplishment were age, work engagement, work reward, and level of workplace. Conclusion: In this study, we identified several factors that can be modified to reduce the risk of burnout among dentists in Thailand.